Android-Based Media Development in Mathematics Lessons - Firdayati, Ulfi; Darwan, Darwan; Kusmanto, Hadi (Jurusan Tadris Matematika IAIN Syekh Nurjati Cirebon, 2021)
This study aims to develop Android-based media for learning the orm applications by developing designs to attract students to learn independently. The application used in this study is the Smart Apps Creator (SAC). This media development uses the research and development (R&D) method according to Sugiyono by using the Potential and Problem steps, Gathering Information, Product Design, Design Validation, Design Improvement, Product Testing, Product Revision, and Usage Trials. The validation results by the media expert were 0.84 with the criteria